Imperfect Corrections or Correct Imperfections? Psychometric Corrections in Meta-Analysis. Issue 2 (27th May 2015) - Oswald, Frederick L.; Ercan, Seydahmet; McAbee, Samuel T.; Ock, Jisoo; Shaw, Amy
<x content-type="archive" xml:space="preserve">Abstract</x> There is understandable concern by LeBreton, Scherer, and James (2014) that psychometric corrections in organizational research are nothing more than a form of statistical hydraulics. Statistical corrections for measurement error variance and range restriction might inappropriately ratchet observed effects upward into regions of practical significance and publication glory—at the expense of highly questionable results.